PERDA SYARIâAH UNTUK PENANGGULAN HIV/AIDS - Hidayanto, Fajar (Al-Mawarid Jurnal Hukum Islam, 2006)
The cases of HIV/AIDS that happen in Indonesia tend to increase every year. This problem needs to be solved as soon as possible.One of government policy to overcome it is to legislate the Shariâah Acts or to implement the Shariâah local acts in Indonesia. According to the writer of the article, there is an expectation to decrease, to solve and to minimize the cases of HIV/AIDS victims in Indonesia if the Shariâah acts or the Shariâah local acts implement in Indonesia. In this sense, it is clearly that the the religious law could be an alternative to response the problem of society. Kata kunci: perda, syariâah, HIV/AIDS, dan solusi